Comparative efficacy of solvents in removing intratubular sealer during root canal retreatment: a CLSM and SEM study - Punnama Metheekul; Kallaya Yanpiset; Wassana Wichai; Jeeraphat Jantarat (BMC Oral Health)
Abstract Background Complete removal of root canal filling materials is essential for retreatment success. Patent dentinal tubules improve disinfectant and sealer penetration, enhancing sealing. Solvents aid removal by softening gutta percha and sealer. Due to cytotoxicity concerns with synthetic solvents, natural alternatives like GuttaClear—a solvent from citrus fruit extracts—are gaining attention for their efficacy and biocompatibility. This study evaluates AH Plus sealer solubility in organic solvents and their ability to remove intratubular residues during retreatment. Methods For intratubular sealer assessment, 51 human mandibular premolars with oval straight root canals were filled with with rhodamine B-labeled AH Plus sealer and allocated to four groups: retreatment without solvent (n = 16), with xylene (n = 16), with GuttaClear (n = 16), and a negative control which did not receive the root canal retreatment (n = 3). Confocal laser scanning microscopy (CLSM) analysis quantified residual sealer penetration in 1-mm root slices at 2, 5, and 8 mm from the apex. Scanning electron microscopy (SEM) examination validated dentinal tubule cleanliness in six additional roots (n = 2 per retreatment group). For solubility evaluation, 72 standardized AH Plus sealer discs were distributed across three immersion solvents (xylene, GuttaClear, distilled water; n = 24 each) and four immersion intervals (2, 5, 10, 20 min; n = 6 per subgroup). Solubility percentage was calculated based on pre- and post-immersion weights. Two-way ANOVA was used for statistical analysis in CLSM analysis and solubility test. Results CLSM analysis demonstrated that the non-solvent group retained the highest percentage of residual sealer, followed by xylene and GuttaClear groups across all root levels. GuttaClear demonstrated superior removal efficacy compared to xylene in the apical region (p < 0.05). SEM evaluation confirmed these findings, revealing fewer occluded dentinal tubules in the GuttaClear group compared to xylene and non-solvent groups. GuttaClear exhibited the highest AH Plus sealer dissolving efficacy, followed by xylene and distilled water, with GuttaClear effectively dissolving AH Plus sealer at all timepoints while xylene required extended exposure (p < 0.05). Conclusion Both xylene and GuttaClear demonstrated superior efficacy in dissolving AH Plus sealer and reduced residual sealer in dentinal tubules during the retreatment of oval root canals, with GuttaClear being more effective in the apical third. Clinical trial number Not applicable.